A Systematic Derivation of Stochastic Taylor Methods for Stochastic Delay Differential Equations - Norhayati, Rosli; Arifah, Bahar; S. H., Yeak; X., Mao (Universiti Sains Malaysia, 2013)
This article demonstrates a systematic derivation of stochastic Taylor methods for solving stochastic delay differential equations (SDDEs) with a constant time lag, r > 0. The derivation of stochastic Taylor expansion for SDDEs is presented. We provide the convergence proof of one–step methods when the drift and diffusion functions are Taylor expansion. It is shown that the approximation solutions for SDDEs converge in the L2-norm.